Diagnosis and treatment of pulmonary Aspergillus infection secondary to empyema complicated with lung cancer: a case report - Zhu, Chen; Liu, Xiuli; Gu, Ying; Shen, Yuyao; Jiang, Tingshu (Frontiers in Medicine, 2025)
BackgroundThis study aimed to explore the clinical characteristics, diagnosis, and management of Invasive Pulmonary Aspergillosis (IPA) complicating empyema in a patient with lung cancer.Case presentationWe analyzed the clinical manifestations, bronchoscopic findings, and therapeutic approaches, including anti-infective and anti-tumor treatments, in a patient diagnosed with IPA-associated empyema and lung cancer. Histopathological examination of bronchoscopic biopsy specimens confirmed pulmonary adenocarcinoma, while bronchoalveolar lavage fluid cultures identified Aspergillus fumigatus. Following the development of secondary empyema, comprehensive anti-infective and anti-tumor therapies were administered, leading to disease control. IPA-associated empyema complicating lung cancer represents a rare clinical scenario.ConclusionIn patients presenting with IPA, the potential coexistence of lung cancer should be considered. An integrated approach combining antifungal therapy and active anti-tumor treatment is essential for managing such cases.